1995
DOI: 10.1002/1097-0142(19950815)76:4<579::aid-cncr2820760407>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tumor pathology with duration of survival of north american patients with hepatocellular carcinoma

Abstract: Background. Several of the large studies addressing prognosis and survival from hepatocellular carcinoma (HCC) have been from Europe and Asia, but only a few have emanated from North America. Survival statistics from other parts of the world may not be applicable to the North American population because of etiologic, demographic, cultural, lifestyle, and intangible differences. The current study investigated the survival experience and histologic correlates of North American patients with HCC and compared find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 22 publications
(1 reference statement)
1
47
0
2
Order By: Relevance
“…In a multicenter study in northern Italy (23), a reduced gastric cancer risk was observed in women with later menopause and longer duration of fertile life. The favorable prognostic value of females, mainly younger patients, has been shown not only in gastric carcinoma (24), but also in tumors of other organs such as lung, liver, and colorectum (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study in northern Italy (23), a reduced gastric cancer risk was observed in women with later menopause and longer duration of fertile life. The favorable prognostic value of females, mainly younger patients, has been shown not only in gastric carcinoma (24), but also in tumors of other organs such as lung, liver, and colorectum (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The HCCs were graded according to a modified version of the Edmonson and Steiner classification. 22,23 Specifically, modified Edmondson and Steiner grades 1 and 2 were defined as well-differentiated, grade 3 as moderately differentiated and grade 4 as poorly differentiated. In tumours exhibiting several regions of differentiation, grading was established according to the highest grade observed.…”
Section: Lesion Confirmationmentioning
confidence: 99%
“…18,19 We aimed to identify genes involved in the dedifferentiation of hepatocellular carcinoma. We previously showed that chromosomal instability increases parallel to dedifferentiation of hepatocellular carcinoma.…”
Section: -31mentioning
confidence: 99%
“…17 This is of clinical interest because morphological grading has been shown to correlate with survival. 18,19 Elucidation of the processes causing dedifferentiation of hepatocellular carcinoma is required because hepatocellular carcinoma dedifferentiated in more than half of patients within 7-34 months. 20,21 Investigations into the genomic and mRNA expression level have been attempted to provide insight into these processes, but a combined analysis has not yet been carried out.…”
mentioning
confidence: 99%